Dimorphic metabolic and endocrine disorders in mice lacking the constitutive androstane receptor - Lukowicz, Céline (Sci Rep, 2019)
Metabolic diseases such as obesity, type II diabetes and hepatic steatosis are a public health concern in developed countries. The metabolic risk is gender‐dependent. The constitutive androstane receptor (CAR), which is at the crossroads between energy metabolism and endocrinology, has recently emerged as a promising therapeutic agent for the treatment of obesity and type 2 diabetes. In this study we sought to determine its role in the dimorphic regulation of energy homeostasis. We tracked male and female WT and CAR deficient (CAR−/−) mice for over a year. During aging, CAR−/− male mice developed hypercortisism, obesity, glucose intolerance, insulin insensitivity, dyslipidemia and hepatic steatosis. Remarkably, the latter modifications were absent, or minor, in female CAR−/− mice. When ovariectomized, CAR−/− female mice developed identical patterns of metabolic disorders as observed in male mice. These results highlight the importance of steroid hormones in the regulation of energy metabolism by CAR. They unveil a sexually dimorphic role of CAR in the maintenance of endocrine and metabolic homeostasis underscoring the importance of considering sex in treatment of metabolic diseases.